Планета чудовищ: [повесть] / Э. Веркин - Веркин Эдуард (Космические приключения, 2009)
Экземпляры: ОРФ (2010) / Инвентарный номер: 46006 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 32 / ББК: 84(2Рос=Рус)6